Bile metabolites of polycyclic aromatic hydrocarbons (PAHs) in three species of fish from Morocco - Baali, Ayoub; Kammann, Ulrike; Hanel, Reinhold; El Qoraychy, Ikram; Yahyaoui, Ahmed (Environmental Sciences Europe, 2016)
Polycyclic aromatic hydrocarbons (PAH) are environmental contaminants that pose significant risk to health of fish. Environmental pollution of fish is a topic of rising attention in Morocco. However, only few studies have been carried out so far, describing the potential threat of organic pollution to Moroccan aquatic ecosystem. Two polycyclic aromatic hydrocarbon (PAH) metabolites, 1-hydroxypyrene (1-OH-Pyr) and 1-hydroxyphenanthrene (1-OH-Phen), were identified and quantified from the bile of 18 European eels (Anguilla anguilla ), 7 Moray (Muraenidae), and 28 Conger eels (Conger conger) collected from Moulay Bousselham lagoon and Boujdour coast. The bile metabolites were separated by high-performance liquid chromatography with fluorescence detection. The present study aims to compare the levels of PAH metabolites in fish from the lagoon and the open sea and to compare levels of PAH metabolites in different fish species. - The major metabolite present in all fish was 1-hydroxypyrene (<LOD-15.56 ng/mL) with lower concentration of 1-hydroxyphenanthrene (<LOD-9.6 ng/mL). These concentrations of PAH metabolites are low compared to studies published before. The data confirm the importance of 1-hydroxypyrene as the key PAH metabolite in fish bile and suggest that the European eel is an ideal species for monitoring PAHs in Moroccan waters. The present study provides valuable information on concentrations of PAH metabolites in fish from Morocco, especially for the first time for Conger eels and Moray.